S1D:6 Targeting plasma cells and their precursors by immunoablation versus bortezomib plus rituximab in systemic lupus erythemtosus. (21st March 2018) - Alexander, T; Hoyer, B; Cheng, Q; Khodadadi, L; Taddeo, A; Klotsche, J; Thiel, A; Burmester, G; Radbruch, A; Arnold, R; Hiepe, F
Abstract : Purpose: To investigate the therapeutic relevance of targeting long-lived plasma cells (PC), which contribute to the chronicity of SLE through continuous secretion of pathogenic antibodies, using immunoablation with antithymocyte-globulin (ATG) in the context of haematopoietic stem cell transplantation (HSCT) or proteasome inhibition with Bortezomib. Methods: Prospective analysis of outcome in 10 SLE patients after receiving autologous HSCT between 1998 and 2012 and 8 SLE patients after receiving a median 2 cycles (range 1–4) of Bortezomib 1.3 mg/m2 between 2009 and 2012 at the Charité – University Medicine Berlin. Multiparametric flow cytometry was applied to characterise peripheral blood or bone marrow PC subsets and B cells. Autoantibodies and vaccine titres were investigated with ELISA. Results: In all HSCT treated patients clinical remissions (SLEDAI <3) were achieved, accompanied by a complete normalisation of anti-dsDNA antibody titres (92.6% reduction) and a significant reduction of antinuclear antibodies and vaccine titres (measles 82.3%). Peripheral blood B and PCs were virtually absent and bone marrow PCs largely depleted (97.6% reduction, n=1) shortly after HSCT and regenerating B cells almost exclusively displayed a naïve phenotype. Upon proteasome inhibition, clinical improvements were associated with a significant reduction of anti-dsDNA autoantibodies (69.3%) and vaccine titers (measles 32.5%). While B cell number/phenotype remained stable, both bone marrow and circulating PC were significantly reduced ( 50%) but rapidly regenerated after proteasome inhibition, which could be prevented by additional rituximab therapy in one patient applied. Conclusions: Although less prominent compared to HSCT, proteasome inhibition with Bortezomib promoted a therapeutically relevant PC depletion in refractory SLE. Nevertheless, for sustained responses, PC depletion needs to be combined with therapeutic strategies targeting their precursor B cells, e.g. with rituximab, as indicated by our preclinical studies in murine lupus.